Challenges and solutions of medical residency: the example of Iran - Behrooz Rahimi; Ali Nemati; Behzad Tadayon; Mahmood Samadpour; Amin Biglarkhani (BMC, 2024)
Abstract Background Medical residency constitutes a highly demanding and taxing phase in the professional journey of physicians. Factors such as low income, excessive workloads, and uncertainty regarding their career trajectory can contribute to diminished job satisfaction among residents. Neglecting this issue can have enduring negative effects on the quality and quantity of healthcare services provided. This research aims to explore the challenges encountered during medical residency and propose viable solutions. Methods In this qualitative study conducted in 2023, interviews were employed to identify challenges, facilitators, barriers, and potential solutions associated with transitioning from residency to a job. In the qualitative section, a purposive selection process led to the inclusion of 26 interviewees, and for the Delphi method, 17 experts were purposefully chosen at three hierarchical levels: macro (Ministry of Health), intermediate (university), and executive (hospital). Qualitative data underwent analysis using a conceptual framework, while Delphi data were subjected to quantitative analysis. Results The qualitative analysis revealed five general themes with 13 main categories and 70 sub-categories as challenges, two general themes as facilitators, and barriers to the transition from residency to a job. Additionally, eight main categories with 52 interventions were identified as solutions to overcome these barriers. In the Delphi stage, the number of proposed solutions was streamlined to 44 interventions. The most significant challenges identified in this study included high workload during residency, low income, career-related uncertainties, issues related to welfare services, and challenges in education and communication. Conclusion The decline in residents' willingness, coupled with the substantial work and financial pressures they face, poses a serious threat to the healthcare system, necessitating significant reforms. Transitioning from residency to a full-fledged job emerges as a potential avenue to address a substantial portion of the expressed needs. Implementing these reforms demands resolute determination and collaboration with sectors beyond the healthcare system, integrated into a comprehensive national healthcare plan that considers the country's capabilities.